Chlorine toxicity: A matter that should be of concern to all swimmers, coaches, and parents (Swimming Science Journal)
In the course of preparing materials for the Swimming Science Journal, the author came across the following articles concerning chlorinated pools. Abstracts of contents and appropriate comments are included below. Please read the discussion points and articles that follow the abstracts.